2020
DOI: 10.1161/jaha.120.016766
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Outcomes in Patients With Different Etiologies of Intracerebral Hemorrhage: A Multicenter Cohort Study

Abstract: Background We aimed to investigate the association between blood pressure (BP) and outcomes in intracerebral hemorrhage (ICH) subtypes with different etiologies. Methods and Results A total of 5656 in‐hospital patients with spontaneous ICH were included between January 2012 and December 2016 in a prospective multicenter cohort study. Etiological subtypes of ICH were assigned using SMASH‐U (structural lesion, medication, amyloid angiopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…On the other hand, mixed ICH patients seemed to have a higher incidence of ICH than only HTN ICH occurrences ( Pasi et al, 2018 ) suggesting a possible protective effect of HTN in CAA. Another study reported similar results; CAA patients with HTN had better clinical outcomes after ICH events ( Zhang et al, 2020 ). Treating with anti-hypertensive therapies was shown to reduce incidence of ICH and stroke in HTN patients ( Qureshi et al, 2001 ) and was also found to decrease ICH incidence in CAA patients ( Arima et al, 2010 ).…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, mixed ICH patients seemed to have a higher incidence of ICH than only HTN ICH occurrences ( Pasi et al, 2018 ) suggesting a possible protective effect of HTN in CAA. Another study reported similar results; CAA patients with HTN had better clinical outcomes after ICH events ( Zhang et al, 2020 ). Treating with anti-hypertensive therapies was shown to reduce incidence of ICH and stroke in HTN patients ( Qureshi et al, 2001 ) and was also found to decrease ICH incidence in CAA patients ( Arima et al, 2010 ).…”
Section: Discussionmentioning
confidence: 64%
“…However, arteriography and venography study showed normal arterial and venous walls. Amyloid angiopathy commonly occurs in old age and in a patient with high blood pressure 8 . However, there was no evidence of amyloid deposition on MRI.…”
Section: Discussionmentioning
confidence: 92%
“…Amyloid angiopathy commonly occurs in old age and in a patient with high blood pressure. 8 However, there was no evidence of amyloid deposition on MRI. Neoplastic tissues are hypervascular, and blood vessels are usually fragile that can undergo necrosis, and put the patients at risk of intracerebral bleeding.…”
Section: Discussionmentioning
confidence: 93%
“…Blood pressure management is deemed critical to prevent hematoma expansion and blood pressure monitoring with systemic arterial pressure should be considered. American Heart Association recommends lowering systolic blood pressures in the setting of acute ICH to 140 is safe while maintaining mean arterial pressures greater than 65 [ 56 ]. Furthermore, critical care management in the emergency department should include monitoring for any change in the neurological examination.…”
Section: Managementmentioning
confidence: 99%